NURSING TECHNOLOGY SUPPORTING FAMILY INVOLVEMENT IN CRITICALLY ILL PATIENTS: A SYSTEMATIC REVIEW - Sumardi, Sulistia Nur; Ismail, Suhartini; Kaloeti, Dian Veronika Sakti (Faculty of Nursing, Universitas Hasanuddin, 2023)
Background: Family involvement in the care of critically ill patients positively impacts treatment outcomes and patient well-being. Nursing technology has become an essential tool in facilitating family engagement Aims: This study aims to conduct a systematic review of nursing technology that supports family involvement in critically ill patients. Methods: This article utilized a systematic review method. Articles were assessed using the JBI Critical Appraisal Checklist. The instruments were the JBI Critical Appraisal Checklist for Randomized Controlled Trials and the JBI Critical Appraisal Checklist for Cohort Studies. Literature from the past five years was obtained from four databases: Science Direct, Scopus, Springer Link, and ProQuest. Results: Out of 148 articles, 15 were analyzed. Various technologies (such as web-based platforms, tablets, SMS tools, and video conferencing) were used to provide information, enhance decision-making, and provide virtual access to family conferences. Although interventions varied,